Advances in Antidiabetic Drugs Targeting Insulin Secretion - Ding, Yanting; Li, Yilian; Chen, Qin; Niu, Bing (Current Pharmaceutical Design, 2018)
Background: Diabetes mellitus (DM) is a disease of systemic metabolic disorders caused by the decrease of secretion or sensitivity of insulin. In recent years, the study of insulin-related drug targets and the development of new drugs have become the popular topic of current medical research, and studies have shown that multiple signaling pathways are associated with diabetes treatment. At present, some new drugs based on the new target design have been listed on the market and have achieved good hypoglycemic effect. However, most of the drugs are still in the clinical or pre-clinical stage. The efficacy and safety of the drugs need further clinical validation. Objective: This article will introduce the advancements of targets and drugs to promote insulin secretion.
Keywords: antidiabetic drugs